Effects of Dietary Standardized Ileal Digestible Isoleucine:Lysine Ratio on Nursery Pig Performance - A. B. Clark; M. D. Tokach; J. M. DeRouchey; S. S. Dritz; K. Touchette; R. D. Goodband; J. C. Woodworth (Kansas Agricultural Experiment Station Research Reports, 2016)
A total of 560 nursery pigs were used in 2 experiments to evaluate the effects of increasing dietary standardized ileal digestible (SID) Isoleucine:Lysine (Ile:Lys) ratio on growth performance. In Exp. 1, 280 pigs (PIC 327 × 1050, initially 14.9 lb BW) were fed experimental diets for 12 d with 8 replications and 5 pigs per pen. In Exp. 2, 280 pigs (DNA Genetics Line 600 × Line 241, initially 13.3 lb BW) were fed experimental diets for 18 d with 8 replications and 5 pigs per pen. In both experiments, pens were allotted to 1 of 7 dietary treatments in a randomized complete block design. The 7 dietary treatments were 40, 44, 48, 52, 54, 58, and 63% SID Ile:Lys ratio. After the experimental diet feeding period, a common diet was fed for 14 d. Diets in both phases were fed in meal form. For Exp. 1, from d 0 to 12 when experimental diets were fed, ADG and ADFI improved (ADG, linear, P<0.001; and ADFI, quadratic, P<0.017) and F/G became poorer (quadratic, P<0.041) as SID Ile:Lys ratio increased. For ADG, the quadratic (QP), broken-line linear (BLL), and broken-line quadratic (BLQ) models reported maximum ADG at 64.7, 52.0, and 52.0% SID Ile:Lys ratio, respectively. For ADFI, the BLL breakpoint occurred at 50.6% and the QP predicted maximum ADFI at 56.2% SID Ile:Lys ratio. In Exp. 2, from d 0 to 18 when experimental diets were fed, ADG and ADFI improved (quadratic, P<0.009) with no significant differences for F/G as SID Ile:Lys ratio increased. For ADG, the BLL and QP had similar fit with breakpoints/maximums occurring at 51.8% SID Ile:Lys ratio and 58.3% SID Ile:Lys ratio, respectively. For ADFI, the QP reported maximum ADFI at 57.2% SID Ile:Lys ratio and the BLQ breakpoint occurred at 52.0% SID Ile:Lys. In summary, these experiments demonstrate that the SID Ile requirement for 15 to 25 lb nursery pigs is approximately 52% of Lys for ADG and ADFI using broken line models and can be as high as 64% of Lys using quadratic models. A slight quadratic effect was observed in feed efficiency for Exp. 1, however in Exp. 2, there were no appreciable differences detected in F/G. The Ile requirement for 15 to 25 lb pigs was found to be similar to NRC (2012) requirement estimates.
Keywords: isoleucine; growth; nursery pigs; swine